AIAA Propulsion and Energy 2019 Forum 2019
DOI: 10.2514/6.2019-4201
|View full text |Cite|
|
Sign up to set email alerts
|

An assessment on the unsteady flow distortion generated by an S-duct intake

Abstract: Closer integration between the fuselage and the propulsion system is expected for future aircraft to reduce fuel consumption, emissions, weight and drag. The use of embedded or partially embedded propulsion systems may require the use of complex intakes. However, this can result in unsteady flow distortion which can adversely affect the propulsion system efficiency and stability. This works assesses the characteristics of the unsteady flow with a view to the potential flow distortion presented to the compressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Studies revealed that flow distortion is associated with the boundary layer thickness. A thicker incoming boundary layer generates high levels of total pressure distortion [229] and swirl distortion, as it can generate early separation, leading to the growth of the contra-rotating vortices at the AIP [230]. Along with the thickness of the boundary layer, the orientation also plays a role; depending on the boundary layer orientation, compatibility issues may arise between the intake and the compressor [230].…”
Section: Current and Future Perspectives In Engine-intake Aerodynamic...mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies revealed that flow distortion is associated with the boundary layer thickness. A thicker incoming boundary layer generates high levels of total pressure distortion [229] and swirl distortion, as it can generate early separation, leading to the growth of the contra-rotating vortices at the AIP [230]. Along with the thickness of the boundary layer, the orientation also plays a role; depending on the boundary layer orientation, compatibility issues may arise between the intake and the compressor [230].…”
Section: Current and Future Perspectives In Engine-intake Aerodynamic...mentioning
confidence: 99%
“…A thicker incoming boundary layer generates high levels of total pressure distortion [229] and swirl distortion, as it can generate early separation, leading to the growth of the contra-rotating vortices at the AIP [230]. Along with the thickness of the boundary layer, the orientation also plays a role; depending on the boundary layer orientation, compatibility issues may arise between the intake and the compressor [230]. An asymmetric boundary layer can significantly change the spatial distributions of the lateral swirl switching mode and the vertical oscillatory mode of the bulk swirl [23].…”
Section: Current and Future Perspectives In Engine-intake Aerodynamic...mentioning
confidence: 99%